Stability and structure of three-way DNA junctions containing unpaired nucleotides. - Leontis, N B (1991)
Non-paired nucleotides stabilize the formation of three-way helical DNA junctions. Two or more unpaired nucleotides located in the junction region enable oligomers ten to fifteen nucleotides long to assemble, forming conformationally homogeneous junctions, as judged by native gel electrophoresis. The unpaired bases can be present on the same strand or on two different strands. Up to five extra bases on one strand have been tested and found to produce stable junctions. The formation of stable structures is favored by the presence of a divalent cation such as magnesium and by high monovalent salt concentration. The order-disorder transition of representative three-way junctions was monitored optically in the ultraviolet and analyzed to quantify thermodynamically the stabilization provided by unpaired bases in the junction region. We report the first measurements of the thermodynamics of adding an unpaired nucleotide to a nucleic acid three-way junction. We find that delta delta G degrees (37 degrees C) = +0.5 kcal/mol for increasing the number of unpaired adenosines from two to three. Three-way junctions having reporter arms 40 base-pairs long were also prepared. Each of the three reporter arms contained a unique restriction site 15 base-pairs from the junction. Asymmetric complexes produced by selectively cleaving each arm were analyzed on native gels. Cleavage of the double helical arm opposite the strand having the two extra adenosines resulted in a complex that migrated more slowly than complexes produced by cleavage at either of the other two arms. It is likely that the strand containing the unpaired adenosines is kinked at an acute angle, forming a Y-shaped, rather than a T-shaped junction.